Feasibility assessment of crowdsourcing slogans for promoting household waste segregation in India: a cross-sectional study - Krishnan, Kavya; Sahoo, Krushna Chandra; Kalyanasundaram, Madhanraj; Singh, Surya; Srinivas, Asha; Pathak, Ashish; Stålsby Lundborg, Cecilia; Atkins, Salla; Rousta, Kamran; Diwan, Vishal (Frontiers in Public Health, 2023)
Introduction Crowdsourcing is an emerging technique to engage or access a wider set of experts and multiple stakeholders through online platforms, which might effectively be employed in waste management. Therefore, we assessed the feasibility of the crowdsourcing method to provide an alternative approach that can improve household waste segregation using an “online-slogan-contest”. Methods The contest was promoted via targeted emails to various governmental and non-governmental organizations and through social media platforms for around 4 weeks (25 days). The entries were received through a Google form. The slogans were assessed by the experts and analyzed using content analysis methods. Results Total 969 entries were received from different geographic regions in India. Of that, 456 were in English and 513 in Hindi. Five themes of waste segregation emerged from the received slogans: (1) Community awareness, responsibility, and support, (2) Significance of household waste segregation, (3) Use of separate dustbins, (4) Health and well-being, and (5) Environment and sustainability. Discussion Crowdsourcing approaches can be used by local authorities for improving waste management approaches and are recommended as these involve a wider audience within a short time frame. Moreover, this approach is flexible and integrating crowdsourcing approaches strengthens our understanding of existing waste management activities.